Auditing Pricing and Auditor Change: an Investigation of Low-balling Effect in the UK - Li, Ye (2009)
Public authority, the media and academic researchers have expressed concern over the price discounting behavior followed by an initial auditor change. This audit low balling effect is significant since it is criticized as a threat to auditor independence. This study investigates the impact of auditor change in audit fees, and to determine whether the low balling behavior takes place in the UK audit market. Tests are conducted for a sample of 250 public listed companies selected from London Stock Exchange FTSE 350 index over the period 2004-2008. The results suggest here is a positive association between auditor change in the short term and audit pricing, and this positive relationship appears to persist for auditor change in the longer term with increasing level of audit fee. Therefore, this study concludes that low balling behavior is not observed for at least a part of UK audit market.